Am I a student and/or entrepreneur? Multiple identities in student entrepreneurship. Issue 2 (13th February 2017) - Nielsen, Suna Løwe; Gartner, William B.
Abstract : Purpose: The purpose of this paper is to study different aspects and tensional forces that play a role in the internal and contextual negotiation that takes place within students in the exploration of the possible identity of entrepreneur. It expands the knowledge of how the university context influences student entrepreneurial processes from a multiple identity perspective. The findings are related to discussions of entrepreneurship education. Design/methodology/approach: A conceptual paper that presents a framework on student entrepreneurial identity sense making that is grounded in a multiple identity perspective. The framework is illustrated by ten narrative cases on student entrepreneurship. Findings: The framework suggests four different ways students make sense of identity in the process of exploring the entrepreneurial identity along with their university studies. In this process students negotiate between the two identities of "student" and "entrepreneur", both demanding in time, effort and commitment, and they in different manners struggle with balancing university belonging and entrepreneurial distinctiveness. Originality/value: The framework serves as a point of departure for discussing the psychological processes and tensions associated with students' entrepreneurial identity construction, and what it means to entrepreneurship education. It is suggested that universities to a higher degree have to view themselves as psychological institutional moratoriums and thus as platforms of identity explorations rather than deterministic systems preparing students for certain careers to support students in becoming entrepreneurs.